Essays in migration economics: A host country perspective on receiving and integrating immigrants - Linea Hasager (University of Copenhagen, Department of Economics, 2020)
This Ph.D. dissertation consists of four self-contained chapters. Although the chapters study different research questions and the applied methods differ, they all share a common focus on how host countries absorb immigrants into society.
Keywords: 330